TEM Characterization of Helium Bubbles in T91 and MNHS Steels Implanted with 200 keV He Ions at Different Temperatures*Supported by the National Basic Research Program of China under Grant Nos 2010CB832902 and 91026002, and the National Natural Science Foundation of China under Grant No U1232121. (July 2015) - Wang, Ji; Gao, Xing; Wang, Zhi-Guang; Wei, Kong-Fang; Yao, Cun-Feng; Cui, Ming-Huan; Sun, Jian-Rong; Li, Bing-Sheng; Pang, Li-Long; Zhu, Ya-Bin; Luo, Peng; Chang, Hai-Long; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> Modified novel high silicon steel (MNHS, a newly developed reduced-activation martensitic alloy) and commercial alloy T91 are implanted with 200 keV He2+ ions to a dose of 5 × 1020 ions/m2 at 300, 450 and 550°C. Transmission electron microscopy (TEM) is used to characterize the size and morphology of He bubbles. With the increase of the implantation temperature, TEM observations indicate that bubbles increase in size and the proportion of 'brick shaped' cuboid bubbles increases while the proportion of polyhedral bubbles decreases in both the steel samples. For the samples implanted at the same temperature, the average size of He bubbles in MNHS is smaller than that in T91. This might be due to the abundance of boundaries and precipitates in MNHS, which provide additional sites for the trapping of He atoms, thus reduce the susceptibility of MNHS to He embrittlement.